REVITALISASI BUDAYA MESATUA BALI MELALUI MEDIA DIGITAL - I Gede Yudha Pratama (ARTic, 2019)
This research was compiled based on a visual design study on the revitalization of the Mesatua Bali culture which was divided into 3 (three) periods, namely: the first Balinese Mesatua (oral) culture, the second period Mesatua Balinese culture (written literature), and the third period Mesatua Bali culture (digital visual). The Mesatua Bali culture is an oral tradition culture carried out by parents to their children. In this study begins by sharpening the substance and structure of research problems designed through the structure of the thinking of researchers. The design of the structure of thought focuses on the purpose of research, namely, to find out the causes and consequences of changes in the revitalization of Balinese Mesatua culture. The method used in this study is descriptive qualitative method, in order to meet objective data needs in conducting studies on the revitalization of Balinese Mesatua culture, this study uses data collection techniques through observation, interviews, and documentation. Surgery for object research is carried out starting from observing aspects of actors, technology and targets. Furthermore, an analysis of the stimuli generated starting from space, time and atmosphere (desa-kala-patra) and the human sensory field. In the final stage a study of visual elements in visual objects is carried out starting from the composition of balance, continuity, combination, unity, typography to color. Then it is compared based on each period of the object of research with 3 (three) levels of values, namely, essential, important, and desirable to analyze aspects that influence the revitalization of the Balinese Mesat culture and dissect what are new, what remains, what was lost, and what changed from the 3 (three) periods to the revitalization of the Balinese Mesatua culture. The results of this study indicate that there is a phenomenon of change in each period from the revitalization of Balinese Mesatua culture. The phenomenon of changes occurring in the revitalization of the Balinese culture from oral to become a visual form (design) is influenced and dilaterbelak by several factors, namely: factors of actors, target factors, technological factors along with factors of space, time, atmosphere (desa-kala-patra) different in each period.